2015
DOI: 10.1080/10426914.2015.1059445
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Plasma Channel Expansion in Micro-EDM

Abstract: Micro-EDM is derived from traditional EDM (electrical discharge machining), and widely used in the micro fabrication field. By using narrow-width pulse power generators, micro-EDM can be applied to machining work with smaller gaps and at low energy levels, which demonstrates a different electro-discharge process and material erosion characteristics, compared with traditional EDM. Through in-depth study on micro-EDM and MHD (magnetic fluid dynamics), a comprehensive plasma model has been established consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…EDM is a nonconventional technology in that material is removed from the workpiece as a result of a series of discharges. During a single electrical discharge, the temperature inside the plasma channel is estimated to be between 6000 and 7000 K [50]. Heat flux causes melting and evaporation of both the workpiece and the working electrode.…”
Section: Resultsmentioning
confidence: 99%
“…EDM is a nonconventional technology in that material is removed from the workpiece as a result of a series of discharges. During a single electrical discharge, the temperature inside the plasma channel is estimated to be between 6000 and 7000 K [50]. Heat flux causes melting and evaporation of both the workpiece and the working electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the machining performance can be improved using graphene nanofluid as the dielectric [ 75 ]. Studies on plasma channel expansion, nano-powder-mixed sinking and milling in micro-EDM were also carried out [ 76 , 77 ].…”
Section: Powder-mixed Edmmentioning
confidence: 99%
“…where τ nuc is the nucleation time (s). Through Clausius-Clapeyron equation, the bubble pressure of nucleation can be obtained as follows [20]:…”
Section: Formation and Expansion Of Discharge Plasmas Of Micro-edmmentioning
confidence: 99%
“…The initial temperature of plasma T p can be obtained from Equation (11). It has been found that the initial pressure of discharge plasma is as high as 1010 Pa, the initial radius is about 0.18 µm, and the initial temperature is as high as 17,304 K [20]. These are expected to be adopted as initial conditions in the iterative calculation of plasma expansion and heating stages.…”
Section: Formation and Expansion Of Discharge Plasmas Of Micro-edmmentioning
confidence: 99%